Workshop Penulisan Artikel Ilmiah Aspek Pembelajaran Bagi Guru SD Se-Kecamatan Tualang Kabupaten Siak - Silvia, Silvia Permatasari; Auzar, Auzar; Mustafa, M. Nur; Sinaga, Mangatur; Burhanuddin, Dudung; Zulhafizh, Zulhafizh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The professional ability that a teacher must have is being able to write articles, especially in terms of learning. Teachers still have difficulty in overcoming problems in the classroom. In addition, teachers also lack the knowledge, understanding, and skills in writing articles, especially learning articles. This makes teachers have less interest in writing scientific articles, especially aspects of learning. The purpose of this activity is not only to obtain credit points for promotion but also for accreditation purposes, but more importantly, to increase teacher professionalism. Scientific writings containing research results, assessment results, ideas, and other teacher's works have great potential as a means of communication for the world of education. The methods used are lectures, questions and answers, discussions, and guidance services. The results obtained indicate that the trainee teachers have additional knowledge and understanding of writing scientific articles on aspects of learning and skills in writing scientific articles on aspects of learning. Through this activity, teachers produce scientific articles on aspects of learning that are worthy of publication in scientific journals.